Ethical Dilemma and Moral Distress - Pina, João Paulo Azenha (Journal of the Portuguese Society of Anesthesiology, 2019)
The author seeks to discuss the use and the meaning of the term moral distress considering the circumstances in which it is applied and its importance in the process of ethical deliberation in clinical practice. According to the literature and within the concepts of bioethics, the author concludes that, from his point of view, there is no place for moral distress as an emotion or phenomenon that arises after the deliberation and the clinical decision, however it is acceptable that moral distress appears as an inevitable and normal emotion during the discussion of the ethical dilemma. Thus, in his opinion, it is not the moral distress that can be blamed for the compassion fatigue or moral residue.